Longitudinal association of childhood physical activity and physical fitness with physical activity in adolescence: insights from the IDEFICS/I.Family study - Becky Breau; Mirko Brandes; Toomas Veidebaum; Michael Tornaritis; Luis A. Moreno; Dénes Molnár; Lauren Lissner; Gabriele Eiben; Fabio Lauria; Jaakko Kaprio; Stefaan De Henauw; Wolfgang Ahrens; et al. (BMC, 2022)
Abstract Background This study aimed to examine associations of early childhood physical fitness and physical activity (PA) with PA during later childhood/early adolescence while accounting for gender differences. Methods We selected data of N = 4329 children from the IDEFICS/I. Family cohort (age 2.4-11.7 years) with data on baseline fitness and accelerometer measurements. At baseline, physical fitness tests were conducted including Flamingo balance, Backsaver sit and reach, Handgrip strength, Standing Long Jump, 40-m sprint and 20-m Shuttle run (to estimate cardio-respiratory fitness levels). PA was measured with Actigraph accelerometers over 3 days at baseline (ActiTrainer or GT1M) and 7 days at follow-up (GT3X). Evenson cutpoints were used to determine moderate-to-vigorous PA (MVPA) time, and children with ≥60mins/day of average MVPA were deemed as having met WHO guidelines at baseline and follow-up. Linear and logistic regressions were performed to examine longitudinal associations between meeting WHO guidelines, MVPA, and physical fitness tests at baseline with meeting WHO guidelines and MVPA at follow-up. Models were conducted on the entire sample, the sex-stratified sample, and stratified by sex and pubertal status at follow-up. Results Results showed that meeting WHO guidelines for MVPA at baseline was positively associated with MVPA (Standardized Beta (B) = 0.13, 95%CI:(5.6;11.1)) and meeting WHO guidelines at follow-up for the entire sample (OR = 2.1, 95%CI:(1.5; 3.14), and stratified by males (OR = 2.5, 95%CI:(1.5; 4.1)) and females (OR = 1.8, 95%CI:(1.0; 3.2)). This was also found for both male pre/early pubertal and pubertal groups but only in the female pre/early pubertal group, and not the female pubertal group (MVPA: B = .00, 95%CI:(− 6.1; 5.6), WHO: OR = 0.61, 95%CI:(0.23;1.6)). Models indicated that Standing Long jump, 40-m sprint, Shuttle run and Flamingo balance at baseline were associated with MVPA and meeting the guidelines at follow-up. Conclusions Meeting WHO guidelines and certain fitness tests at baseline were strongly associated with MVPA and meeting WHO guidelines at follow-up, but this association varied with sex and pubertal status. Consequently, these findings underline the importance of ensuring sufficient physical activity in terms of quality and quantity for children at the earliest stages of life. Trial registration ISRCTN62310987.